2016 IEEE 57th Annual Symposium on Foundations of Computer Science (FOCS) 2016
DOI: 10.1109/focs.2016.50
|View full text |Cite
|
Sign up to set email alerts
|

Rectangular Kronecker Coefficients and Plethysms in Geometric Complexity Theory

Abstract: We prove that in the geometric complexity theory program the vanishing of rectangular Kronecker coefficients cannot be used to prove superpolynomial determinantal complexity lower bounds for the permanent polynomial.Moreover, we prove the positivity of rectangular Kronecker coefficients for a large class of partitions where the side lengths of the rectangle are at least quadratic in the length of the partition. We also compare rectangular Kronecker coefficients with their corresponding plethysm coefficients, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…For this reason, K. Mulmuley suggested that we investigate the barriers of the method of shifted partials in the unpadded setting (although Mulmuley himself anticipated our answer). Similar concerns were shown after the results of [IP17] and [BIP19] on the Geometric Complexity Theory program, and were partially addressed in [GIP17], exploiting the same homogenization result of [Nis91] that we use in this work.…”
supporting
confidence: 61%
“…For this reason, K. Mulmuley suggested that we investigate the barriers of the method of shifted partials in the unpadded setting (although Mulmuley himself anticipated our answer). Similar concerns were shown after the results of [IP17] and [BIP19] on the Geometric Complexity Theory program, and were partially addressed in [GIP17], exploiting the same homogenization result of [Nis91] that we use in this work.…”
supporting
confidence: 61%
“…Via the standard projection C n×n → C m×m , we can view X n−m 11 per m as an element of the bigger space ∈ Sym n (C n×n ) * . (Sometimes the padding is achieved by using a linear form different from X 11 , e.g., but this is irrelevant, see [26,Appendix]. )…”
Section: Introductionmentioning
confidence: 99%
“…Proof. This is proved by a finite calculation for all cases but (3, 3) as Thm 1.10(a) in [IP17]. Exactly the same calculation can be used to also prove the result for the additional partition (3, 3).…”
Section: No Occurrence Obstructionsmentioning
confidence: 63%
“…The papers [IP17, BIP19] rule out occurrence obstructions for families, but only in ranges where they would give very strong new algebraic circuit lower bounds, so that we expect it to be difficult to find multiplicity obstructions in those cases. Note also that [IP17,BIP19] are only dealing with padded polynomials, for which [KL14] guarantees λ to have a very restricted shape.…”
Section: Representation Theoretic Obstructionsmentioning
confidence: 99%
See 1 more Smart Citation